Grand Opera, Musical Brothel: COMUS’s Nightbloom, the CEE, and the Innovation of Canadian Opera - Renihan, Colleen (Intersections, 2021)
In the 1970s and 1980s, a flurry of activity in music theatre—a genre combining the genres of musical theatre, experimental theatre, and opera—prompted the creation of several new Canadian opera/music theatre companies specializing in crossover work, along with a creative outpouring of original genre-defying pieces. In this paper, I explore this period of generic experimentation in the history of Canadian opera, focusing on the work of the innovative company COMUS Music Theatre, founded in 1975 in Toronto. The company sought to revolutionize music theatre by presenting works that engaged with other media, as well as with theatre, popular music, dance, and performance art. COMUS Music Theatre’s production of Nightbloom (February 1984) serves as an example of the company’s generic innovation and experimentation. Through musical and textual analysis, and interviews with key figures in its creation, I explore the bold ways that COMUS Music Theatre succeeded in imagining a new way forward for opera singers and for music theatre in Canada in the 1970s.